Starch/banana pseudostem biocomposite films for potential food packaging applications - Othman, Siti Hajar; Tarmiti, Nurul Atiqah Najhah; Shapi'i, Ruzanna; Zahiruddin, Siti Mariam; Tawakkal, Intan Syafinaz; Basha, Roseliza (North Carolina State University * College of Natural Resources, 2020)
Banana pseudostems (BP) are a promising cellulose source that remains underutilized despite its potential to be formed as biodegradable food packaging material. This work was directed towards utilizing BP waste in a powder form to produce potential food packaging material that is environmentally friendly. A solvent casting method was used to produce starch/BP films at different BP percentage compositions (0, 10, 20, 30, and 40 wt% on the dry basis of starch). The effects of different percentage compositions of BP in starch on the morphology, optical, mechanical, and barrier properties of the films were investigated. The optical and mechanical properties of the starch films decreased with the addition of BP. However, the mechanical and barrier properties of the films improved with the increase in BP composition. An optimum percentage composition of 40 wt% BP powder can be utilized to produce starch/BP films for potential food packaging application.